Knowledge, Attitudes, Practices and Some Characteristic Features of People Recovered from COVID-19 in Turkey - Yakut, Seda; Karagulle, Burcu; Atcali, Tugce; Ozturk, Yasin; Acik, Mehmet Nuri; Cetinkaya, Burhan (Mdpi, 2021)
Background and objectives: The whole world is spending an extraordinary effort by implementing various measures to control and prevent the COVID-19 pandemic. The effectiveness of the preventive measures is greatly influenced by the public's knowledge, attitudes, and practices (KAP) towards the disease. In this study, KAP values and some characteristic features of people recovered from COVID-19 were determined by conducting a questionnaire survey. Materials and Methods: The questionnaire survey was conducted between 1 and 10 January 2021 on people who recovered from COVID-19 in a total of 150 different locations in Turkey. The questionnaire consisted of 46 questions: 14 for determining demographic and some characteristic features of the participants, and 32 for determining their knowledge, attitudes, and practices. The data obtained were evaluated using descriptive statistics, chi-squared tests, t-tests, and one-way analysis of variance (ANOVA). Results: It was determined that 63% of the participants had at least one chronic illness, 3.9% suffered from the disease twice, and 45.2% changed their smoking habits. The average knowledge score of the participants about COVID-19 was calculated as 10.25 (SD = 2.37; range 0-15). The participants were found to have a high level of knowledge about the symptoms and prevention methods in general, and positive changes in post-illness attitudes and behaviors. However, there was a great instability regarding the drugs and vaccines used in the treatment of COVID-19. Conclusions: This was the first study carried out in Turkey to determine knowledge, attitudes, practices, and some characteristic features of people who recovered from COVID-19. It was suggested that health authorities in the country need to develop more effective strategies and policies to find out permanent solutions in order to control and prevent the COVID-19 pandemic by taking into account the concerns of the public, particularly with regards to the drugs used in the treatment and vaccination.
Keywords: COVID-19; questionnaire; knowledge; attitude; practice